2014
DOI: 10.1111/iej.12303
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of glutamine on LPS‐stimulated human dental pulp cells correlate with activation of MKP‐1 and attenuation of the MAPK and NF‐κB pathways

Abstract: Glutamine exerted an anti-inflammatory effect via activation of MKP-1 and inhibition of the NF-κB and MAPK pathways in LPS-treated HDPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…These data agreed with previous studies indicating occludin function could be regulated in a manner dependent on NF-κB [45, 46]. Meanwhile, it has been suggested that IκBα is associated with MKP-1 dependent negative regulation, which is attributed to modulate the immune response [13, 14]. In a kinetic analysis of IκBα phosphorylation, we found primarily an effect of MKP-1 deficiency on the up-regulation of IκBα activation that led to markedly increased phospho-IκBα levels in Sertoli cells by LPS stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…These data agreed with previous studies indicating occludin function could be regulated in a manner dependent on NF-κB [45, 46]. Meanwhile, it has been suggested that IκBα is associated with MKP-1 dependent negative regulation, which is attributed to modulate the immune response [13, 14]. In a kinetic analysis of IκBα phosphorylation, we found primarily an effect of MKP-1 deficiency on the up-regulation of IκBα activation that led to markedly increased phospho-IκBα levels in Sertoli cells by LPS stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…This observation was in agreement with the findings obtained in PLS analysis ( Figure 6A). The role of the metabolites detected in this study has been described in numerous studies [23][24][25]. Earlier studies have reported The presented values are the mean of four replicates ± SD.…”
Section: Correlation Between Metabolite Profiles and No Inhibitory Acsupporting
confidence: 63%
“…Indeed, we showed that iNOS, probably through NF-kB-dependent signaling cascades, is also involved in the regulation of MYD88 expression in the liver (6). Furthermore, the results of Kim et al (36), Lu et al (37), and Hammami et al (38) suggest that Gln may directly alter iNOS activity in vitro. In accordance with these findings, Esposito et al (39) also found that in ischemia/reperfusion models the beneficial effects of Gln supplementation on the liver were associated with protection against the induction of iNOS in the liver.…”
Section: Discussionmentioning
confidence: 55%